An??lise cinem??tica da marcha de mulheres com dor femoropatelar - Dias, Alesandra Cabreira (2018)
Patellofemoral pain (DFP) is one of the most frequent dysfunctions in the knee, during functional activities such as crouching, climbing and descending stairs among others, reaching 25% of all knee injuries. Multifactorial etiology is associated with biomechanical disorders characterized by deficits in motor control of the trunk and lower limbs during activities in daily life. Thus, the objectives of this work are: 1 - To compare the kinematics of the trunk, pelvis, hip, knee, ankle and foot in women with patellofemoral pain and healthy women during gait; 2 - Compare the range of motion of trunk flexion, inclination and rotation, anteversion, pelvic obliquity and rotation, flexion / extension, abduction / adduction and internal / external rotation of the hip, flexion / extension and valgus / varus of the knee, dorsiflexion / plantar flexion and eversion / reversal of the hindfoot during initial contact, load response, and support phase between females with patellofemoral pain and healthy women during gait; 3 - Compare gait cycle time, cadence, velocity, simple support time, double support and step length between women with patellofemoral pain and healthy women during gait. A total of 270 women were evaluated, 129 in the control group (CG) and 141 in the patellofemoral pain group (PFD), all of them physically active, aged between 18 and 35 years. Compared with the asymptomatic group the cycle time and the percentage of simple support were higher in the PFD group, while the pitch length and velocity were smaller when compared to the healthy group. In the initial contact the control group presented external rotation of the hip and plantar flexion of the ankle, and the DFP internal rotation of the hip and ankle dorsiflexion. In the response the load increased internal hip rotation, greater ankle dorsiflexion, rearfoot eversion and greater angle of progression in external rotation of the DFP foot, compared to GC. The magnitude of the maximum value was greater for ankle dorsiflexion and for the angle of progression in external rotation of the DFP foot. There was more flexion of the trunk, less internal rotation of the hip and dorsiflexion of the ankle in the DFP for magnitude of minimum value. The range of motion in the support phase was greater for internal rotation of the hip in the group.